Clustering of adherence to personalised dietary recommendations and changes in healthy eating index within the Food4Me study. Issue 18 (8th August 2016) - Livingstone, Katherine M; Celis-Morales, Carlos; Lara, Jose; Woolhead, Clara; O'Donovan, Clare B; Forster, Hannah; Marsaux, Cyril FM; Macready, Anna L; Fallaize, Rosalind; Navas-Carretero, Santiago; San-Cristobal, Rodrigo; Kolossa, Silvia; et al.
Abstract: Objective: To characterise clusters of individuals based on adherence to dietary recommendations and to determine whether changes in Healthy Eating Index (HEI) scores in response to a personalised nutrition (PN) intervention varied between clusters. Design: Food4Me study participants were clustered according to whether their baseline dietary intakes met European dietary recommendations. Changes in HEI scores between baseline and month 6 were compared between clusters and stratified by whether individuals received generalised or PN advice. Setting: Pan-European, Internet-based, 6-month randomised controlled trial. Subjects: Adults aged 18–79 years ( n 1480). Results: Individuals in cluster 1 (C1) met all recommended intakes except for red meat, those in cluster 2 (C2) met two recommendations, and those in cluster 3 (C3) and cluster 4 (C4) met one recommendation each. C1 had higher intakes of white fish, beans and lentils and low-fat dairy products and lower percentage energy intake from SFA ( P <0·05). C2 consumed less chips and pizza and fried foods than C3 and C4 ( P <0·05). C1 were lighter, had lower BMI and waist circumference than C3 and were more physically active than C4 ( P <0·05). More individuals in C4 were smokers and wanted to lose weight than in C1 ( P <0·05). Individuals who received PN advice in C4 reported greater improvements in HEI compared with C3 and C1 ( P <0·05). Conclusions: The cluster where the fewest recommendations were met (C4) reported greater improvements in HEI following a 6-month trial of PN whereas there was no difference between clusters for those randomised to the Control, non-personalised dietary intervention.